2024
DOI: 10.1038/s41594-023-01152-y
|View full text |Cite
|
Sign up to set email alerts
|

Pioneer factor Pax7 initiates two-step cell-cycle-dependent chromatin opening

Arthur Gouhier,
Justine Dumoulin-Gagnon,
Vincent Lapointe-Roberge
et al.

Abstract: Pioneer transcription factors direct cell differentiation by deploying new enhancer repertoires through their unique ability to target and initiate remodelling of closed chromatin. The initial steps of their action remain undefined although pioneers were shown to interact with nucleosomal target DNA and with some chromatin remodelling complexes. We now define the sequence of events that provide pioneers with their unique abilities. Chromatin condensation exerted by linker histone H1 is the first constraint on … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 43 publications
0
0
0
Order By: Relevance
“…Depending on the investigator, pioneer factors can be defined in a variety of ways ( 63 ). More recently, it has been suggested that pioneer factors could mediate their effect through a multi-step process that requires passage through cell division to establish open chromatin for other TFs ( 64 ). Several TFs have been indicated to act as pioneer factors for GR, including AP-1, CCAAT-enhancer-binding protein beta (CEBPB), myogenic differentiation 1 (MYOD1), and hepatocyte nuclear factor 4A (HNF4A) ( 27 , 65 67 ).…”
Section: Transcription Factor Crosstalk Mechanisms Of Grmentioning
confidence: 99%
“…Depending on the investigator, pioneer factors can be defined in a variety of ways ( 63 ). More recently, it has been suggested that pioneer factors could mediate their effect through a multi-step process that requires passage through cell division to establish open chromatin for other TFs ( 64 ). Several TFs have been indicated to act as pioneer factors for GR, including AP-1, CCAAT-enhancer-binding protein beta (CEBPB), myogenic differentiation 1 (MYOD1), and hepatocyte nuclear factor 4A (HNF4A) ( 27 , 65 67 ).…”
Section: Transcription Factor Crosstalk Mechanisms Of Grmentioning
confidence: 99%